Pemahaman Mahasiswa Universitas Muhammadiyah Palembang Tentang Persyarikatan Muhammadiyah - Zuhriyah, Zuhriyah; Kholilah, Kholilah; Fitantina, Fitantina; Refangga, Refangga (MOTIVASI, 2019)
ABSTRACT Purpose - This study aims to determine and analyze the understanding of Palembang Muhammadiyah University students towards the Muhammadiyah Association.Design/methodology - This research is a quantitative study, collecting data using a questionnaire. Before the questionnaire was distributed previously carried out trials using validity and reliability. The number of respondents in this study were 234 students. Data analysis using descriptive t test analysis through the help of the SPSS application. Findings - Based on the results of this study, it can be said that in general students of the University of Muhammadiyah Palembang understand about the requirements of Muhammadiyah.